Disruption of Plasmodium falciparum kinetochore proteins destabilises the nexus between the centrosome equivalent and the mitotic apparatus - Li, Jiahong; Shami, Gerald J.; Liffner, Benjamin; Cho, Ellie; Braet, Filip; Duraisingh, Manoj T.; Absalon, Sabrina; Dixon, Matthew W. A.; Tilley, Leann (Nature communications, 2024)
Plasmodium falciparum is the causative agent of malaria and remains a pathogen of global importance. Asexual blood stage replication, via a process called schizogony, is an important target for the development of new antimalarials. Here we use ultrastructure-expansion microscopy to probe the organisation of the chromosome-capturing kinetochores in relation to the mitotic spindle, the centriolar plaque, the centromeres and the apical organelles during schizont development. Conditional disruption of the kinetochore components, Pf NDC80 and Pf Nuf2, is associated with aberrant mitotic spindle organisation, disruption of the centromere marker, CENH3 and impaired karyokinesis. Surprisingly, kinetochore disruption also leads to disengagement of the centrosome equivalent from the nuclear envelope. Severing the connection between the nucleus and the apical complex leads to the formation of merozoites lacking nuclei. Here, we show that correct assembly of the kinetochore/spindle complex plays a previously unrecognised role in positioning the nascent apical complex in developing P. falciparum merozoites. Using Ultra-Expansion Microscopy of the malaria parasite, P. falciparum , Li et al. show that disruption of kinetochore components breaks a nexus between the mitotic spindle and the nascent apical organelles.